HUBUNGAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI ORGANIZATIONAL COMMITMENT PADA BEBERAPA PUSKESMAS DI DKI JAKARTA - Catalia Rafsiah Sari Sari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
This research refers to a previous study conducted by Nicolas Raineri et al., (2012). This research is about “The Impact of Perceived Organizational Support to Organizational Citizenship Behavior mediated by Organizational Commitment on some health centers in Jakarta”. The background of this research is to analyze the Organizational Citizenship Behavior as determining factors of motivation in the health care industry. The purpose of this researchwas to examine the relationship Perceived Organizational Support on Organizational Citizenship Behavior through Organizational Commitment. The design of this research using primary data obtained by distributing questionnaires to 100 employees medical and nonmedical health center in Jakarta.. Data analysis method used in this research is Structural Equation Model (SEM). The results of this research concluded that there is a positiverelationship Perceived Organizational Support on Organizational Citizenship Behavior through Organizational Commitment.Keywords: Perceived Organizational Support, Organizational Citizenship Behavior,Organizational Commitment